1981
DOI: 10.1042/bj1980661
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin A-induced chemiluminescence in rat thymus lymphocytes. Its origin and role in mitogenesis

Abstract: 1. The luminol-dependent chemiluminescence of rat thymocytes responding to concanavalin A can be resolved into glucose-dependent and glucose-independent portions. 2. The glucose-dependent portion, supported by D-glucose and D-mannose oxidation, is inhibited by catalase (200 microgram/ml), amobarbital (1 mM) and hexose analogues that block D-glucose uptake. Thus concanavalin A may activate, transiently, an NAD(P)H oxidase that utilizes reducing equivalents derived from the oxidation of exogenous glucose to give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The synergistic interaction between monocytes and lymphocytes to produce enhanced chemiluminescence has been observed previously (Clement and Lehmeyer, 1983;Hume et al, 1981), and it has also shown that it is the binding of lectins to the cell surface which is the most important initiator of CL (Mookerjee et al, 1980). Two distinct mechanisms are involved in the generation and handling of the excited oxygen species in monocytes and polymorphonuclear leukocytes and this may account for the different response times to PHA-C (Nguyen et al, 1983).…”
Section: Discussionsupporting
confidence: 70%
“…The synergistic interaction between monocytes and lymphocytes to produce enhanced chemiluminescence has been observed previously (Clement and Lehmeyer, 1983;Hume et al, 1981), and it has also shown that it is the binding of lectins to the cell surface which is the most important initiator of CL (Mookerjee et al, 1980). Two distinct mechanisms are involved in the generation and handling of the excited oxygen species in monocytes and polymorphonuclear leukocytes and this may account for the different response times to PHA-C (Nguyen et al, 1983).…”
Section: Discussionsupporting
confidence: 70%
“…Generation of moderate amounts of ROS (reactive oxygen species) by several non-phagocytic leucocytes, including B-lymphocyte cell lines [1][2][3][4], human tonsillar B-lymphocytes [5], thymocytes [6,7], human NK (natural killer) cells [8,9], human peripheral T-lymphocytes [10] and T-lymphocyte cell lines [11], has been described.…”
Section: Introductionmentioning
confidence: 99%
“…Cheson et al (53) reported that reactive oxygen species alone are not enough in the production of CL and suggested that the oxidation of particle components was necessary for CL to occur. Recently, two modes of CL have been distinguished: a glucose-dependent component and a glueose-independent component; the latter associated with formation of intermediates of arachidonic acid mctabolistn via tlic lipoxygenasc pathway (54,55,56). Cheung et al (56) suggest that glucosedependent CL Is elosely related to the activation of NADPH oxidase and is inhibited by scavengers and inhibitors of reactive oxygen speeies.…”
Section: Chemiluminescencementioning
confidence: 99%